2016
DOI: 10.1142/s0218301316300046
|View full text |Cite
|
Sign up to set email alerts
|

2015 Update of the discoveries of nuclides

Abstract: The 2015 update of the discovery of nuclide project is presented. Twenty new nuclides were observed for the first time in 2015. An overall review of all previous assignments was made in order to apply the discovery criteria consistently to all elements. In addition, a list of isotopes published so far only in conference proceedings or internal reports is included.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…This is the sixth update of the isotope discovery project which was originally published in a series of papers in Atomic Data and Nuclear Data Tables from 2009 through 2013 (see for example the first 1 and last 2 papers). Two summary papers were published in 2012 and 2013 in Nuclear Physics News 3 and Reports on Progress in Physics, 4 respectively, followed by annual updates in 2014, 5 2015, 6 2016, 7 2017, 8 and 2018. 9 In 2016 a description of the discoveries from a historical perspective was published in the book "The Discovery of Isotopes -A complete Compilation".…”
Section: Introductionmentioning
confidence: 99%
“…This is the sixth update of the isotope discovery project which was originally published in a series of papers in Atomic Data and Nuclear Data Tables from 2009 through 2013 (see for example the first 1 and last 2 papers). Two summary papers were published in 2012 and 2013 in Nuclear Physics News 3 and Reports on Progress in Physics, 4 respectively, followed by annual updates in 2014, 5 2015, 6 2016, 7 2017, 8 and 2018. 9 In 2016 a description of the discoveries from a historical perspective was published in the book "The Discovery of Isotopes -A complete Compilation".…”
Section: Introductionmentioning
confidence: 99%
“…Two summary papers were published in 2012 and 2013 in Nuclear Physics News 3 and Reports on Progress in Physics, 4 respectively, followed by annual updates in 2014, 5 2015 6 and 2016. 7 The 2016 update included an overall reevaluation to apply the criteria uniformly for all elements. A description of the discoveries from an historical perspective was published last year in the book "The Discovery of Isotopes -A complete Compilation".…”
Section: Introductionmentioning
confidence: 99%
“…4. Discoveries not yet published in refereed journalsEight isotopes ( 96 In,94 Cd, 92 Ag, 90 Pd, 178 Pb, 230 Am, 234 Cm, and 234 Bk) included in the list of isotopes only reported in proceedings or internal reports in last year's update7 have been published in refereed publications this year. While 215 U was still included in this list it was actually published in a refereed journal in 2015 21.…”
mentioning
confidence: 99%
“…More than 3200 different isotopes have been discovered until now. A recent compilation summarized details of the discovery of all isotopes [1][2][3][4][5] including the year, laboratory and country of the discovery as well as the production mechanism used to produce the isotopes. The compilation revealed that more than 25% of these isotopes were formed in heavy-ion induced fusion reactions making this method the most productive way to discover new isotopes.…”
Section: Introductionmentioning
confidence: 99%